2018
DOI: 10.1002/jmv.25287
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sofosbuvir and daclatasvir with or without ribavirin in elderly patients with chronic hepatitis C virus infection

Abstract: Hepatitis C virus (HCV) infection is considered as a major public health problem that, worldwide, chronically affects 170 million people. Elderly patients are more likely than younger patients to have increased duration of infection, increased rate of disease progression, and subsequently increased incidence of advanced liver disease. Natural history models predicted that the prevalence of HCV infection and its chronic sequelae as well as extrahepatic manifestations will eventually increase through the next de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
0
10
1
1
Order By: Relevance
“…42,45 Many infectious agents have been suspected as risk factors for depression, including hepatitis C virus, enterovirus, herpes simplex 1, Epstein-Barr virus, human immunodeficiency virus, varicella-zoster virus, human T-cell lymphotropic virus, Borna disease virus, brucellosis, and Chlamydophila trachomatis. [46][47][48][49][50][51][52] A recent study from Egypt reported that patients treated for chronic hepatitis C decompensated liver cirrhosis using new direct-acting antiviral drugs, which in turn, showed an improvement in liver tests and health-related quality of life. However, longer duration of follow-up for decompensation events are essential.…”
Section: Discussionmentioning
confidence: 99%
“…42,45 Many infectious agents have been suspected as risk factors for depression, including hepatitis C virus, enterovirus, herpes simplex 1, Epstein-Barr virus, human immunodeficiency virus, varicella-zoster virus, human T-cell lymphotropic virus, Borna disease virus, brucellosis, and Chlamydophila trachomatis. [46][47][48][49][50][51][52] A recent study from Egypt reported that patients treated for chronic hepatitis C decompensated liver cirrhosis using new direct-acting antiviral drugs, which in turn, showed an improvement in liver tests and health-related quality of life. However, longer duration of follow-up for decompensation events are essential.…”
Section: Discussionmentioning
confidence: 99%
“…Mi-RNAs, short, non-coding RNAs that regulate gene expression, have been associated with histological features of NAFLD and are readily detected in the circulation. [31][32][33][34][35] The current study showed a significant increase in the level of mi-RNA-122 in NAFLD patients compared to controls, and its level is associated with disease severity from simple steatosis to steatohepatitis. This finding is in agreement with Jampoka et al, 36 who found that serum mi-RNA-122 levels in NAFLD patients were significantly higher than those found in the control group.…”
Section: Discussionmentioning
confidence: 95%
“…Hepatitis C virus infection is a major cause of liver disease in all Egyptian areas, [24][25][26] representing the highest prevalence in the world with about 10% of the population, [27][28][29] the natural history of HCV infection is affected by viral and host factors. 30,31 Hepatitis C virus infection is associated with neuropsychiatric disorders in about 50% of patients and can cause a wide variety of PN, including mainly SFSN and less frequent large LFSN.…”
Section: Discussionmentioning
confidence: 99%